On the management of menopause syndrome patients - N A Tatarova; N P Gavrilova (IP Berlin A.V., 2013)
Research objective. Development of a program of follow-up for women with menopausal metabolic syndrome and cholestasis; determination of the effectiveness of the Femoston in combination with Ursofalk. Materials and methods. 71 women with climacteric syndrome, obesity and cholestasis were under observation; a comprehensive clinical and laboratory examination was carried out, measurement of modified menopausal index before treatment and after 6 months. The results. Positive changes in neurocirculation symptoms and lipid profile were obtained, a statistically significant reduction in transaminases and modified menopausal index, the coagulation parameters remained virtually unchanged. Conclusion. The Femoston and Ursofalk positively influence the climacteric syndrome; normalize lipid profile, having positive influence on the hepatobiliary system. It is appropriate to prescribe this medicine to the patients with menopausal metabolic syndrome and cholestasis.